YURISDIKSI DAN KOMPETENSI PENGADILAN PIDANA INTERNASIONAL - Rabawati, Dwityas Witarti; Nandito S. Wadan , Alessandro; Adhyantara Saba , Excel; Kirania Manu Bulu , Penta; Betekeneng , Kristina (Gapenas Publisher, 2024)
This study discusses the role of the code of ethics in building a reputable profession and enhancing public trust. The research method used is qualitative with a literature study approach. The research found that the code of ethics is an important moral foundation in maintaining the integrity and professionalism of professional members. Strict enforcement of the code of ethics helps increase public trust and preserve professional dignity. However, the study also identifies challenges in implementing the code of ethics, such as low ethical awareness and weak ethical enforcement. Recommendations include increased socialization, development of an adaptive code of ethics, and strict enforcement of ethics.